Rocks and Minerals Flash Cards - "NA" (London DK Children's Publishers, 2022)
About Our World in Pictures Rocks & Minerals Flash Cards Packed with over 100 fun flashcards, you can discover the world's most precious objects, with rocks, gems, minerals and more! Earth's extraordinary minerals, gems, shells, and fossils are all on dazzling display in this essential visual deck of fascinating flashcards for children aged 9+. Our World in Pictures: Rocks & Minerals Flash Cards is an indispensable guide to the natural world's most remarkable treasures, featuring stunning pictures and fast facts that will allow curious young learners to grasp a wealth of knowledge in a fun way! Each card contains snappy and accessible information, displaying each rock or mineral in dazzling detail. The front of the card will show the rock with a clue of what it is. The back reveals the answer, plus a dataset of essential information, ensuring you can recognise sedimentary from sandstone, metamorphic from marble, and pyrite from pearl. You'll discover the unique qualities of each material, together with how it is used in art, industry, architecture, and science.
Keywords: Flashcards